PENGARUH MODEL PEMBELAJARAN GUIDED DISCOVERY TERHADAP MOTIVASI BELAJAR MATERI KERAGAMAN BUDAYA DI SEKOLAH DASAR - Annisa Qomariah Nisa (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2022)
The Guided Discovery model emphasizes the active involvement of students in learning that is oriented towards discovery activities with teacher guidance. This study aims to determine the effect of the Guided Discovery learning model on students' learning motivation. Guided Discovery is directly involved in discovering concepts and principles and the role of the teacher encourages students to have experiences that allow them to discover independently. Changing the mindset of students who only receive complex information from the teacher towards the mindset of students getting information independently. Learning will run well and creatively if the teacher provides opportunities for students to discover concepts, principles, theories, rules, through examples found in the surrounding environment. This study used a quasi-experimental method conducted in class IV. odd semester of the 2022/2023 school year. Data collection techniques using questionnaires. Data analysis used the Kruskal-Wallis test. The results of data analysis obtained that the value of Sig. (2-tailed) is 0.03 <0.05, so it can be concluded that there is a significant influence of the Guided Discovery learning model on students' learning motivation. Keywords: Guided Discovery, Motivation to learn, Cultural diversity